Spectrum, distance spectrum, and Wiener index of wreath products of complete graphs - Donno, Alfredo (Ars mathematica contemporanea, 2017)
We describe the adjacency matrix and the distance matrix of the wreath product of two complete graphs, and we give an explicit computation of their spectra. As an application, we deduce the spectrum of the transition matrix of the Lamplighter random walk over a complete base graph, with a complete color graph. Finally, an explicit computation of the Wiener index is given.
Keywords: matrika sosednosti; razdaljna matrika; razdaljni spekter; spekter; venčni produkt polnih grafov; Wienerjev indeks